Problems of Development of Control Models and Mechanisms in Modern Ecosystems - T. Yu. Serebryakova; E. R. Fatkhullin (Учёт. Анализ. Аудит)
The article is devoted to internal control as one of the management functions and its organisational form, as well as problematic aspects of the formation of control mechanisms in connection with the development of information tools and sources of ecosystem management at all levels. Despite the fact that there is an increase in the number of organizations implementing various control mechanisms, methods and systems, they often do not achieve the goals of obtaining relevant and sufficient information about the state of the controlled object, and the goal of control, which is to provide information support for the process of achieving the effectiveness of management (and control itself), is not achieved. The purpose of the study is to evaluate the theoretical basic approaches to control in order to identify the possibilities of building control mechanisms of modern level for commercial organisations. In the course of the research, such general scientific methods of cognition as a systematic approach, logical generalization, legal and linguistic analysis, and hypothesis were used. Control is an indispensable accompaniment of management activities. A lot depends on its organization, including the effectiveness of management, the timeliness of achieving the intended results, and the progressive development of the business. Control exists in two planes: it is either directly embedded in the technological and managerial processes or it is superstructured and conducted and carried out by specially created bodies that are outside the flow of processes and exercise control “from the outside”. The development of digital technologies imposes features and causes the emergence of certain peculiarities in the formation of control mechanisms, which, on the one hand, gives more opportunities for control, on the other hand, introduces formalism into it, reducing the effectiveness of both its own and the entire organisation in terms of its core activities. The search for a harmonious combination is the main task in organizing effective control in commercial organizations. The results of the study will be useful to researchers and practitioners who study control mechanisms in theoretical and methodological aspects.